PENGARUH IDENTITAS, NILAI DAN AKTIVITAS TERHADAP KEPUTUSAN PEMBELIAN JILBAB PADA BUTIK ALBADA PONTIANAK (STUDI EMPIRIS PADA HIJABERSMOM COMMUNITY PONTIANAK) - admin, SITI KOMARIAH B11110069 (Jurnal Manajemen Update, 2016)
The purpose of this research is to investigate the influence of identity, value, and activity towards a buying decision of Hijab at Albada Boutique Pontianak. In this research, the population was Muslim mothers, members of Hijabersmom Community Pontianak. 100 respondents then were selected to represent the research sample. The method used for this research was an associative study, while questionnaires were used for a data collection purpose. The tool for analysis was IBM SPSS 16. The identity variable was measured through several indicators i.e. appetite, prestige, life style, and the sociala class. The value variable was measured by several indicators, for example the product recognition, reputation, and attractiveness. A activity variable was assessed through hijab class and hijab tutorial via virtual media. A buying decision variable was judged by the customer’s routines in the purchase. The factor behind the purchase decision, confidence to buy products, and stability tobuy product. As a result of discussion, it can be concluded thet the identity variable (X1) had an influence towards a decision to purchase products (Y). it means that identity could encourage respondents in this sample to make a decision to buy products. On the other hand, the value variable (X2) and activity variable (X3) did not give a significant influence towards the decision to purchase products (Y). it means that could not force respondents in this sample to make a decision to buy products.   Keywords:      Identity, Value, Activity, Buying Decision.